The Pinch Technique and its Applications to Non-Abelian Gauge Theories - Cornwall, John M. (Cambridge University Press, 2011)
Non-Abelian gauge theories, such as quantum chromodynamics (QCD) or electroweak theory, are best studied with the aid of Green's functions that are gauge-invariant off-shell, but unlike for the photon in quantum electrodynamics, conventional graphical constructions fail. The pinch technique provides a systematic framework for constructing such Green's functions, and has many useful applications. Beginning with elementary one-loop examples, this book goes on to extend the method to all orders, showing that the pinch technique is equivalent to calculations in the background field Feynman gauge. The Schwinger-Dyson equations are derived within the pinch technique framework, and are used to show how a dynamical gluon mass arises in QCD. Finally the volume turns to its many applications. This book is ideal for elementary particle theorists and graduate students.